Children’s preoperative stress according to the parental presence evaluated by salivary cortisol and mYPAS: quasi-randomized trial* - Silveira, Ketillyn Nayara De Macedo [UNESP]; Alves, Rodrigo Leal [UNESP]; Júnior, Paulo Do Nascimento [UNESP]; Coelho, Monique Antonia [UNESP]; De Barros, Guilherme Antonio Moreira [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: The main objective of this study was to compare stress and anxiety levels in children undergoing surgical procedures with or without parental presence at induction of anesthesia by measuring salivary cortisol levels and applying the mYPAS. Method: Quasi-randomized trial with children aged 5-12 year, with ASA physical status I, II, or III, undergoing elective surgery. According to parents’ willingness, the pair were defined as accompanied or unaccompanied group. Chi-square, Fisher’s exact tests, Student’s t test, Mann-Whitney, Hodges-Lehman and Spearman’s tests were used for statistical analyzes. Results: We included 46 children; 63% were preschool children mostly accompanied by their mothers (80%). The median mYPAS score was 37.5 (quartile range, 23.4-51.6) in unaccompanied children, and 55.0 (quartile range, 27.9-65.0) in accompanied children, with an estimated median difference of +11.8 (95% CI of 0 to 23.4; p = 0.044). There were no significant differences in the mean salivary cortisol levels. Conclusion: The level of anxiety was higher in accompanied children. There were no differences in salivary cortisol levels between both groups. Brazilian Registry of Clinical Trials (ReBEC): RBR-9wj4qvy.
Estresse pré-operatório em crianças de acordo com a presença dos pais avaliada por cortisol salivar e mYPAS: ensaio quase-randomizado
Estrés preoperatorio en niños según la presencia de los padres evaluado mediante cortisol salival y mYPAS: ensayo cuasi-aleatorio
Keywords: Anestesia; Anesthesia; Ansiedad; Ansiedade; Anxiety; Child; Criança; Estresse Psicológico; Estrés Psicológico; Hidrocortisona; Hydrocortisone; Niño; Parent-Child Relations; Psychological; Relaciones Padres-Hijo; Relações Pais-Filho; Stress